Values that influencing green product purchase intention / Erna Smith Epoi - Smith Epoi, Erna (Faculty of Business and Management, 2020)
Green product purchase intention is one of the most well-known issues that being discussed worldwide. The values that were practice by the consumers are one that influenced the purchasing power towards the green product. The rival between the conventional product which is harmful and the green product which could save the earth are being one of the hot topics that could not being shaken off by the consumers no matter if they are in Malaysia or International. Thus, the production company also the government need to know what is the major and minors’ factors that are influencing the green product purchase intention. The purpose of this study is to investigate the values that influencing the green product purchase intention. The independents variables that being applied by the research in this study are egoistic value, biospheric value, altruistic value, terminal value and instrumental value. The method that being used by the researcher to conduct this study is by distributing a questionnaire to 384 respondents based on sample size that mention in chapter 3. Based on the result, the major value that influencing the green product purchase intention is instrumental value and all the independent variables are significant except for the biospheric value and terminal value.